The value of non-sport-specific characteristics for talent orientation in young male judo, karate and taekwondo athletes - Pion, J.; Fransen, J.; Lenoir, M.; Segers, V. (Archives of Budo, 2014)
The present study aims to discriminate young male taekwondo, judo, and karate athletes from two age groups. It is hypothesized that a generic test battery (i.e. consisting of non-sport specific items) can allocate athletes in their respective sports. It is also expected that due to training and experience, differences between sports would be larger in the oldest age group. Material and Methods: Fifty-six highly trained taekwondo, judo, and karate athletes U13 (11.596 ± 0.578 years; n = 30) and U18 (16.097 ± 0.844 years; n = 26) completed five anthropometrical, six physical performance and three motor coordination tests. Discriminant analyses were used to investigate relevant performance measures while MANOVAs were conducted to elucidate the differences between taekwondo, judo and karate. Results: The classification results for both discriminant analyses U13 and U18 showed a perfect classification (100%) of the athletes in their respective sports. U18 showed higher multivariate differences between the three martial arts i.e. for anthropometrical measures (F2.148, P =0.044, ES =0.36), physical performance characteristics (F2.216, P =0.033, ES =0.43) and motor coordination (F6.697, P <0.001, ES =0.49) when compared to their younger counterparts. Judo athletes had the highest scores for sit and reach, handgrip, counter movement jump and balance beam. While taekwondo athletes had the highest scores for sit-ups, sprint 5m and 30m and jumping sideways. Conclusions: Generic talent characteristics allow for a successful discrimination between judo, taekwondo and karate athletes, while the differences between the martial arts profiles are more pronounced in older athletes.